General anesthesia technique and perception of quality of postoperative recovery in women undergoing cholecystectomy: A randomized, double-blinded clinical trial. - Daniel de Carli; José Fernando Amaral Meletti; Neri Edu Urnau Neto; Gabriel Martinez; André Luís Corrêa Kim; Rodrigo Pauperio Soares de Camargo (PLoS ONE, 2020)
BACKGROUND:The two most common general anesthesia techniques are total intravenous anesthesia (TIVA) and venous/inhalation balanced general anesthesia (BGA). It is unclear whether any of these two techniques affect patient perception of the quality of recovery. The aim of this randomized, double-blinded clinical trial was to assess the quality of postoperative recovery of women undergoing laparoscopic cholecystectomy under general anesthesia. We compared patients who received TIVA with those who received BGA. We also evaluated the factors that may decrease patient-perceived quality of postoperative recovery. METHODS:We prospectively recruited 121 women aged 18-65 years who were scheduled for elective laparoscopic cholecystectomy due to cholelithiasis. These patients were randomized to receive TIVA (target-controlled infusion of propofol and remifentanil) or BGA (continuous remifentanil infusion and sevoflurane inhalation). To measure the quality of postanesthetic and postoperative recovery, we administered the Quality of Recovery-40 (QoR-40) questionnaire 24 hours after the patient awoke from anesthesia. RESULTS:All 60 patients in the TIVA group responded to QoR-40 (median, 188 points; minimum 128; maximum 200). Sixty-one patients in the BGA group had a mean QoR-40 score of 186 points (median, 188 points; minimum 146; maximum 200). There was no significant difference in the QoR-40 score between the two groups (p = 0.577). The patients who presented postoperative nausea and vomiting (PONV) and pain had worse perception of the quality of postoperative recovery. CONCLUSIONS:Both TIVA and BGA had a similar effect on the perception of the quality of postoperative recovery in women undergoing elective laparoscopic cholecystectomy. PONV and pain may negatively affect patient perception of the quality of postoperative recovery.